Facial asymmetry in head and neck rhabdomyosarcoma survivors - Schoot, R; Hol, M; Merks, J; Suttie, M; Slater, O; van Lennep, M; Hopman, S; Dunaway, D; Syme-Grant, J; Smeele, M; Zwinderman, K; Caron, H; et al. (Wiley, 2017)
1 Introduction Radiotherapy is essential for achieving and maintaining local control in head and neck rhabdomyosarcoma (HNRMS) patients. However, radiotherapy may cause outgrowth disturbances of facial bone and soft tissue, resulting in facial asymmetry. The aim of this study was to develop a method to visualize and measure facial asymmetry in HNRMS survivors using three‐dimensional (3D) imaging techniques. 2 Methods Facial deformity was evaluated in a multidisciplinary clinical assessment of 75 HNRMS survivors, treated with external beam radiotherapy (EBRT, n = 26) or Ablative surgery, MOulage brachytherapy, and REconstruction (AMORE, n = 49). Individual facial asymmetry was measured using 3D photogrammetry and expressed in a raw asymmetry index and a normalized sex–age–ethnicity‐matched asymmetry signature weight. Facial asymmetry was also compared between British and Dutch controls and between survivors and their matched controls. 3 Results Facial asymmetry was more pronounced with increasing age (P < 0.01) in British controls compared with Dutch controls (P = 0.04). Survivors developed more facial asymmetry than matched controls (P < 0.001). The clinical assessment of facial deformity correlated with the raw asymmetry index (r = 0.60, P < 0.001). 4 Discussion 3D imaging can be used for objective measurement of facial asymmetry in HNRMS survivors. The raw asymmetry index correlated with a clinical assessment of facial deformity. Comparisons between treatment groups seemed inappropriate given the differences in facial asymmetry between British and Dutch controls. In future studies, pretreatment images could act as matched controls for posttreatment evaluation.